Pengaruh Kompensasi, Motivasi, Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Perintis Perkasa Toyota Medan - Fitrah Usfah Amoy; Hasrudy Tanjung; Bahril Datuk S (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
This study in PT Perintis perkasa Toyota Medan. This study aims to determine and analyze the Effect of Compensation, Motivation and Job Satisfaction On Employee Performance At the PT Perintis Perkasa Toyota Medan.This study uses associative Kuantitatif. The population used in this study was 1oo employees. To obtain the necessary data in this study, the author used a technique of distributing questionnaires or questionnaires obtained directly At PT Perintis Perkasa Toyota Medan. As well as the annual report which is owned by the company. Analysis data technique in this research is Using, Outer Loading, AVE, uji F and direct effect.The results of this study indicate that partially, Compensation has no significant positive effect on employee performance, Motivation has no significant positive effect on employeeperformance and Job satisfaction has a significant positif effect on employee performance at PT. Perintis Perkasa Toyota Medan